REVIEW: Research Ethnobotany in Indonesia and the Future Perspectives (Biodiversitas Journal of Biological Diversity, 2008)
Indonesia is not only rich in its biodiversity but it is also well known as a country with high diversity of ethnicities. Each ethnic group has extensive experienced in the utilization and conservation of biological and ecological diversity. This biocultural richness has provided ethnobotanical researchers with endless research opportunities. Ethnobotanical study has a long history in Indonesia and dates back to the early Dutch colonization period when Dutch explorers and naturalists recorded the uses of plants used by the natives for food, medicine, buildings materials, etc. Based on research on Java, Hasskarl (1845) recorded 900 species of plants used by Indonesian communities. Previously, Rumphius (1750) in his monumental book "Herbarium Amboinense", reported the uses of several hundreds plants from Ambon and its vicinity. Recently, Indonesian scientists from both government and non-government organizations have given more attention to the importance of ethnobotany as a means of elaborating traditional knowledge, especially for economically useful and scientifically undiscovered plants. The talk will focus on ethnobotanical research performed by LIPI scientists at the Research Center for Biology in Bogor and the Indonesia Botanic Gardens. During the last 20 years, since the Indonesia' Ethnobotanical Museum was established. Indonesian scientists have documented the importance of ethnobotany, ethnomedicine, ethnomycology, ethnoentomology, and ethnoecology for conservation of traditional knowledge in relation to the economic botany and to other applied sciences. The meaning and scope of ethnobotany and its status including the future prospects, its contribution to the exploitation and conservation will be discuses in this paper.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: ethnobotany, ethnomedicine, ethnomycology, ethnoecology, traditional knowledge, use of plants, Indonesia.